Involvement of NF-κB/IL-6 Pathway in the Processing of Colorectal Carcinogenesis in Colitis Mice - Hang Yang; Haili Qi; Jingli Ren; Jing Cui; Zhenfeng Li; Helge L. Waldum; Guanglin Cui (Hindawi Limited, 2014)
Nuclear factor-kappaB (NF-κB)/interleukin (IL-6) pathway links chronic inflammation to colitis associated cancer (CAC). In this study, we examined the dynamic temporal changes of the NF-κB/IL-6 pathway during the procession of experimental CAC mouse model. Mice were sacrificed after induction for 14, 16, 18, and 22 weeks for the examination of tumor burden, inflammation degree, and protein level of NF-κB and IL-6 in bowel tissues. The results showed that tumor burden and inflammation severity in the bowels were gradually increased over the observed time-points. The expressions of IL-6 and NF-κB proteins were gradually increased after induction of dysplastic lesions over times. These data provide new information on the dynamic temporal changes of NF-κB/IL-6 pathway in relation to CAC development that may be relevant in the design of future investigations of therapeutic interventions to effectively target CAC processes.